Comparative analysis of e-cigarette prevalence and influencing factors among adolescents in Jiangsu Province, China - Fan, Jiannan; Mao, Tao; Zhen, Shiqi; Xu, Yan; Qu, Chen (Frontiers in Public Health, 2023)
Objective The objectives of this study were to investigate electronic cigarette (e-cigarette) and cigarette use in Jiangsu Province, China, by analyzing the two-year trends of e-cigarette using and to explore the factors influencing the experimentation and use of e-cigarettes. Methods We conducted a cross-sectional study following the standard methodology of the Global Youth Tobacco Survey in 2019 and 2021. A three-stage cluster sampling design was applied. Eighty-two schools in 14 districts (counties) in Jiangsu Province were surveyed. All computations were performed using the SPSS 21.0 complex samples procedure. Multivariate logistic regression was used to explore the factors influencing e-cigarette experimentation and use. Results A total of 12,410 and 12,880 students were surveyed in 2019 and 2021, respectively. E-cigarette experimentation increased from 9.34% in 2019 to 13.07% in 2021 (P < 0.001). E-cigarette use increased from 2.23% in 2019 to 3.74% in 2021 (P < 0.001). The main factors associated with e-cigarette use were cigarette experimentation (OR = 2.700, P < 0.001); male gender (OR = 1.416, P = 0.011); junior high school students (OR = 1.551, P = 0.005) and vocational high school students (OR = 1.644, P = 0.001); more pocket money per week (OR1 = 1.214, P = 0.187; OR2 = 1.686, P = 0.001); exposure to second-hand smoke (SHS) at home (OR = 1.239, P < 0.001); exposure to e-cigarette advertising (OR = 1.855, P < 0.001); believe SHS is harmful (OR = 0.933, P = 0.026); closest friends smoking (OR = 2.501, P < 0.001); believe smoking makes youth look more attractive (OR1 = 1.469, P = 0.040; OR2 = 1.305, P = 0.049); believe tobacco helps youth feel more comfortable in social situations (OR1 = 2.161, P < 0.001; OR2 = 1.635, P = 0.001); will use an e-cigarette product if offered by best friends (OR = 1.322, P < 0.001); intend to use an e-cigarette product in the next 12 months (OR = 1.486, P < 0.001). Conclusion E-cigarette use among adolescents has been on the rise in recent years. E-cigarette use is associated with past cigarette use and a strong desire to smoke. It is crucial to take health education and tobacco control efforts to reduce adolescents' e-cigarette use rate.